2018
DOI: 10.18632/oncotarget.25729
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity of FLT3-ITD detected by high-throughput amplicon sequencing correlates with adverse prognosis in acute myeloid leukemia

Abstract: In acute myeloid leukemia (AML), internal tandem duplications (ITDs) of FLT3 are frequent mutations associated with unfavorable prognosis. At diagnosis, the FLT3-ITD status is routinely assessed by fragment analysis, providing information about the length but not the position and sequence of the ITD. To overcome this limitation, we performed cDNA-based high-throughput amplicon sequencing (HTAS) in 250 FLT3-ITD positive AML patients, treated on German AML Cooperative Group (AMLCG) trials. FLT3-ITD status determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 73 publications
3
42
0
1
Order By: Relevance
“…It has been previously reported that, compared with patients harboring no DNMT3A mutations, patients carrying DNMT3A mutation were found to have higher CD34 + , CD15 + and HLA-D + rates (29). Furthermore, another previous study revealed that patients carrying FLT3-ITD mutations exhibited higher rates of CD34 + and CD38 + compared with patients without this mutation (30). Therefore, chemotherapy efficacy was compared between the four groups in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…It has been previously reported that, compared with patients harboring no DNMT3A mutations, patients carrying DNMT3A mutation were found to have higher CD34 + , CD15 + and HLA-D + rates (29). Furthermore, another previous study revealed that patients carrying FLT3-ITD mutations exhibited higher rates of CD34 + and CD38 + compared with patients without this mutation (30). Therefore, chemotherapy efficacy was compared between the four groups in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…In our cohort, two FLT3-ITD mutations of 36bp in length (detected by classical molecular techniques in our laboratory) were not called by any of the NGS gene panels tested in this study, which means that conventional diagnostics techniques are still essential for hematological malignancies diagnosis [81]. NGS difficulty for long FLT3-ITD detection has been reported before [62] [82]; this is because current NGS chemistries employ short reading sequencing (read length 50-300bp) and this makes it prone to lose structural variants such as long indels [83] [84]. In support of this observation, in our cohort, the three variants missed by SureSeq panels (sequenced at shorter read length than the other panels, 150bp vs >200bp), were indels.…”
Section: Common Sequencing Errors Detected In the Ngs Panelsmentioning
confidence: 76%
“…A high mutant/wild-type ratio appears to have a major impact on the prognostic relevance [29]. Patients with more than one ITD had a significantly shorter OS and RFS [30]. Retrospective validation study of the ELN-2017 guidelines on the classification for AML with NPM1 and FLT3-ITD genotypes demonstrated that the ELN-2017 was more accurate to distinguish prognosis in patients with newly diagnosed AML [25].…”
Section: Flt3mentioning
confidence: 96%